Survey of the Relationship Between Demographic Characteristics and Organizational Citizenship Behavior in Nurses in Hamadan Educational Centers - Amir Sadeghi; Mehrdad Maleki Jamasbi; Hiva Azami; Manoochehr Karami; Zahra Marziyeh Hassanian (Hamadan University of Medical Sciences, 2019)
Background: Nurses are the most effective pillars of the hospital to improve the quality of services. Their organizational citizenship behaviors are an important factor for improving patient's nursing care. Organizational Citizenship Behaviors (OCB) can prevent additional system costs. The present study was an attempt to determine the relationship between demographic characteristics and OCB of nurses in Hamadan educational centers. Methods: This descriptive-analytic correlational study was conducted in 2016-17. The sample was 200 nurses selected from five educational centers by stratified random sampling method. Data gathering tool were Demographic Information and Organizational Citizenship Behavior of Podsakoff Questionnaires. Data were analyzed by SPSS 21 and using descriptive and analytical statistics (T-test, ANOVA and Pearson correlation coefficient). Results: The results showed that a relatively favorable level of nurses' OCB. There were statistically significant relationship between OCB of nurses with age and work experience respectively (r = 0/20 and P<0/005) and (P<0/029 and r = 0/16). Mean score of Courtesy was 4.03±0.5, Conscientiousness 4.0±0.5, Magnanimity 3.83±0.4, Civic Virtue 3.33±3.8, Altruism 3.83±0.4 and the mean score of OCB was 3.8±0.3. Conclusion: Organizational citizenship behavior of nurses increases with increasing their age and work experience. Therefore, to take advantage of the OCB in hospitals, intensive attention should be paid to training younger nurses and supporting them.